Screening of wild okra (Abelmoschus esculentus) against yellow vein mosaic and enation leaf curl diseases - SANTHIYA, S; YADAV, RAMESH KUMAR; LATA, SUMAN; SHARMA, BRIJ BIHARI; TALUKDAR, AKSHAY; GHOSH, AMALENDU; GHOSH, AMALENDU; VAISHALI, C; JANANI, R (The Indian Journal of Agricultural Sciences, 2022)
Okra yellow vein mosaic (OYVMD) and enation leaf curl diseases (OELCuD) are the most important biotic diseases which cause yield and quality loss in okra (Abelmoschus esculentus (L.) Moench). Therefore, development of viral resistance varieties and lines become important breeding objective worldwide. Wild relatives are the natural source for disease and pest resistance. Hence an experiment was conducted at research farm of ICAR-Indian Agricultural Research Institute, New Delhi during rainy (kharif) season 2020 and for screening of 24 wild genotypes to identify the resistance source for OYVMD and OELCuD diseases of okra. PDI (Percent disease incidence) for OYVMD varied from 3.12–93.72, while PDI for OELCuD ranged from 0.00–83.29. The area under disease progress curve for both the diseases indicated that the rate of disease incidence was in increasing trend with the growth of the crop. Based on the natural epiphytotic screening A. moschatus (IC 141055), A. tetraphyllus (IC 90476-1) and A. caillei (Sikkim) were 3 top most genotypes from different species which showed very less incidence of OYVMD and no incidence of OELCuD. These genotypes were grouped in highly resistant category for both the diseases; other genotypes grouped in this category were A. moschatus (EC 360900), A. tetraphyllus (IC 90515 and IC 470735). These genotypes can be used further for interspecific breeding programme and resistant variety development in okra.